Intestinal and hepatic contributions to the pharmacokinetic interaction between gamithromycin and rifampicin after single‐dose and multiple‐dose administration in healthy foals. (8th January 2018) - Berlin, S.; Wallstabe, S.; Scheuch, E.; Oswald, S.; Hasan, M.; Wegner, D.; Grube, M.; Venner, M.; Ullrich, A.; Siegmund, W.
Summary: Background: Standard treatment of foals with severe abscessing lung infection caused by Rhodococcus equi using rifampicin and a macrolide antibiotic can be compromised by extensive inhibition and/or induction of drug metabolising enzymes (e.g. CYP3A4) and transport proteins (e.g. P‐glycoprotein), as has been shown for rifampicin and clarithromycin. The combination of rifampicin with the new, poorly metabolised gamithromycin, a long‐acting analogue of azithromycin and tulathromycin with lower pharmacokinetic interaction potential, might be a suitable alternative. Objectives: To evaluate the pharmacokinetic interactions and pulmonary distribution of rifampicin and gamithromycin in healthy foals, and to investigate the cellular uptake of gamithromycin in vitro. Study design: Controlled, four‐period, consecutive, single‐dose and multiple‐dose study. Methods: Pharmacokinetics and lung distribution of rifampicin (10 mg/kg) and gamithromycin (6 mg/kg) were measured in nine healthy foals using LC‐MS/MS. Enzyme induction was confirmed using the 4β‐OH‐cholesterol/cholesterol ratio. Affinity of gamithromycin to drug transport proteins was evaluated in vitro using equine hepatocytes and MDCKII‐cells stably transfected with human OATP1B1, OATP1B3 and OATP2B1. Results: Rifampicin significantly (P<0.05) increased the plasma exposure of gamithromycin (16.2 ± 4.77 vs. 8.57 ± 3.10 μg × h/mL) by decreasing the total body clearance. Otherwise, gamithromycin significantly lowered plasma exposure of single‐ and multiple‐dose rifampicin (83.8 ± 35.3 and 112 ± 43.1 vs. 164 ± 96.7 μg × h/mL) without a change in metabolic ratio and half‐life. Gamithromycin was identified as an inhibitor of human OATP1B1, OATP1B3 and OATP2B1 and as a substrate of OATP2B1. In addition, it was extracted by equine hepatocytes via a mechanism which could be inhibited by rifampicin. Main limitations: Influence of gamithromycin on pulmonary distribution of rifampicin was not evaluated. Conclusion: The plasma exposure of gamithromycin is significantly increased by co‐administration of rifampicin which is most likely caused by inhibition of hepatic elimination.